DETERMINAN PERILAKU WANITA MELAKUKAN DETEKSI DINI KANKER SERVIKS DI KABUPATEN LAMPUNG SELATAN - Siti Mariam; Atikah Adyas; William Arisandi (Universitas Malahayati Lampung, 2020)
ABSTRACT : DETERMINANTS OF WOMEN BEHAVIOR IN THE EARLY DETECTION OF CANCER SERVICES IN LAMPUNG SELATAN DISTRICT IN 2020 Introduction : Cervical cancer is the most common cancer in women with an estimated 530,000 new case. The problem facing cervical cancer prevention is the low coverage of early cervical cancer detection rates. In South Lampung in 2018 the number of women of childbearing age of 30-50 years who had undergone IVA examination was 44,913 people (30.5%) with positive results of 624 cases (1.39%).Method : This type of research is quantitative. Analytical research design with cross-sectional approach. The population is all WUS in South Lampung Regency as many as 148,499 people with a sample of 170 respondents. Data analysis used univariate analysis with percentages, bivariate analysis with Chi Square and multivariate analysis with multiple logistic regression predictive models.Result : The results showed that there was a relationship between the supporting factors namely knowledge (p = 0.016), attitude (p = 0.014) and education (p = 0.015) with the behavior of women doing early detection of cervical cancer. There is a relationship between the reinforcing factors of husband / family support (p = 0.001), the role of health workers (p = 0.001) and friend support (0.003) with the behavior of women doing early detection of cervical cancer. There is a relationship between enabling factors for access to information (p = 0.001), access to health services (p = 0,000) and affordability (p = 0.036) and the behavior of women in early detection of cervical cancer. The most dominant variable related to the behavior of women doing early detection of cervical cancer is the variable access to health services with an OR value of 15.46..Conclusion : For this reason, it is hoped that the Puskesmas in South Lampung will continue to mobile to the villages to get closer to the target access to health services with the availability of available resources even though BPJS cannot cover the cost of IVA examinations anymore. Continue to increase promotion efforts through Information and Education Communication (IEC) on early detection of cervical cancer by the IVA method.. Keywords : Determinant, Behavior, Early Detection of Cervical Cancer, Age Women Lush (WUS) INTISARI : DETERMINAN PERILAKU WANITA MELAKUKAN DETEKSI DINI KANKER SERVIKS DI KABUPATEN LAMPUNG SELATAN TAHUN 2020 Latar Belakang : Kanker serviks merupakan kanker paling sering keempat pada wanita dengan perkiraan 530.000 kasus baru, masalah yang menghadang dalam penanggulangan kanker serviks tersebut adalah masih rendahnya angka cakupan deteksi dini kanker serviks. Di Lampung Selatan pada tahun 2018 jumlah wanita usia subur 30-50 tahun yang telah dilakukan pemeriksaan IVA sebanyak 44.913 orang (30,5%) dengan hasil positif sebanyak 624 kasus (1,39%). Metode Penelitian : Jenis penelitian adalah kuantitatif. Desain penelitian analitik dengan pendekatan crosssectional. Populasi adalah semua WUS yang berada di Kabupaten Lampung Selatan sebanyak 148.499 orang dengan jumlah sampel 170 responden. Analisis data menggunakan analisis univariat dengan persentase, analisis bivariat dengan Chi Square dan analisis multivariat dengan regresi logistic berganda model prediktif.Hasil : Hasil penelitian menunjukkan bahwa ada hubungan faktor pendukung yaitu pengetahuan (p=0,016), sikap (p=0,014) dan pendidikan (p=0,015) dengan perilaku wanita melakukan deteksi dini kanker serviks. Ada hubungan faktor penguat dukungan suami/keluarga (p=0,001), peran petugas kesehatan (p=0,001) dan dukungan teman (0,003) dengan perilaku wanita melakukan deteksi dini kanker serviks. Ada hubungan faktor pemungkin akses informasi (p=0,001), akses menuju ke pelayanan kesehatan (p=0,000) dan keterjangkauan biaya (p=0,036) dengan perilaku wanita melakukan deteksi dini kanker serviks. Variabel yang paling dominan berhubungan dengan perilaku wanita melakukan deteksi dini kanker serviks adalah variabel akses ke pelayanan kesehatan dengan nilai OR sebesar 15,46.Kesimpulan : Diharapkan Puskesmas di Lampung Selatan tetap melakukan mobile ke desa untuk mendekatkan akses sasaran ke pelayanan kesehatan dengan ketersediaan sumber daya yang ada meskipun BPJS tidak dapat mengcover biaya pemeriksaan IVA lagi. Terus meningkatkan upaya promosi melalui Komunikasi Informasi dan Edukasi (KIE) tentang deteksi dini kanker serviks dengan metode IVA. Kata Kunci : Determinan, Perilaku, Deteksi Dini kanker Serviks, Wanita Usia Subur (WUS)